1979
DOI: 10.1677/joe.0.0800259
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and Control of Prolactin Receptors in the Mammary Gland and Liver of Virgin, Pregnant and Lactating Rats

Abstract: Prolactin receptors were identified and partially characterized in the mammary gland of the rat. The binding of 125I-labelled ovine prolactin to a subcellular particulate fraction of rat mammary gland decreased between days 30 and 100 of age. Over the same period, binding to the liver increased and there was a significant negative correlation between prolactin binding in the two tissues. Binding to the mammary gland was low during pregnancy, increased in early lactation and declined after the litters were wean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 16 publications
5
24
1
Order By: Relevance
“…Given these data and our present findings, it appears that the suppressive effect of P on PRLR expression is restricted to the pregnant state. The stimulation of PRLR expression by E 2 has previously been attributed to its indirect effect on PRL secretion from the pituitary (Sheth et al 1978, Hayden et al 1979. However, here we show that E 2 has a direct positive effect on pPRLR expression, specifically in mammary epithelial cells, during hypoprolactinemia induced by co-administered Bromo.…”
Section: Discussioncontrasting
confidence: 60%
“…Given these data and our present findings, it appears that the suppressive effect of P on PRLR expression is restricted to the pregnant state. The stimulation of PRLR expression by E 2 has previously been attributed to its indirect effect on PRL secretion from the pituitary (Sheth et al 1978, Hayden et al 1979. However, here we show that E 2 has a direct positive effect on pPRLR expression, specifically in mammary epithelial cells, during hypoprolactinemia induced by co-administered Bromo.…”
Section: Discussioncontrasting
confidence: 60%
“…In the mammary gland of the cycling rat, the number of PRL-R is increased by estrogen and PRL [11], but progesterone lowered the level of PRL-RL mRNA. Progesterone acts as a suppressor of the PRL-R gene expression [18,21,22].…”
Section: Effect Of Ovarian Steroids and Prlmentioning
confidence: 89%
“…The withdrawal of circulating progesterone causes an increase in the number of mammary PRLRs in pregnant mice and rats [9,10]. In virgin rats, PRL binding to the mammary gland is increased by estrogen and PRL [11]. It still remains unclear whether the decrease in the number of PRL-R, observed during early pregnancy, is regulated by ovarian steroids and PRL, and whether this regulation occurs at the level of transcription.…”
Section: Growthmentioning
confidence: 99%
“…These differential expression patterns of the 84 kD PRL-R in spleen and thymus suggest that regulation of PRL-R levels is tissue specific. Similarly, Hayden et al (1979) found a negative correlation between the number of PRL binding sites in the mammary gland and in the liver. They showed that the binding of '251-labeled oPRL to rat mammary gland microsomes decreased between 30 and 100 days of age; whereas, binding to liver microsome increased at these ages.…”
Section: Discussionmentioning
confidence: 71%